Using "space-time of action" to assess changes in accessibility: the example of Bogotá between 1993 and 2009 - Florent Demoraes; Vincent Gouëset; Mégane Bouquet (Cybergeo)
The purpose of this study is to understand changes to household members’ access to place of activity, against the backdrop of urban and socio-demographic transformation. In particular, it seeks to establish whether adults are currently disadvantaged by residing in a location which, in terms of daily mobility, is better suited to their children, or whether other factors are at work, depending particularly on the household’s position in the social hierarchy. It further seeks to understand how mobility conditions have changed over time depending where individuals reside in the city. To this end, it puts forward a new concept called “space-time of action” and proposes a way of mapping it. Drawing on data from two surveys in Bogotá (Colombia) in 1993 and in 2009, “space-times of action” are here used to study joint changes to co-residing working adults’ and children’s access to place of work or study. It details how the space-times of action were devised, before then discussing their advantages and limitations.